2019
DOI: 10.1002/adsu.201900100
|View full text |Cite
|
Sign up to set email alerts
|

Solar Heat‐Enhanced Energy Conversion in Devices Based on Photosynthetic Membranes and PEDOT:PSS‐Nanocellulose Electrodes

Abstract: convert solar energy into electricity by leveraging the complex process of photosynthesis, useful both as energy generators and sensors for various physical inputs. [1][2][3][4][5][6][7][8][9] With accelerating climate change and growing demand for energy, such bio-based methods have been identified as a promising route toward "green" energy. [10] Thylakoid membranes (TMs), the compartments inside chloroplasts, algae, and cyanobacteria in which the light-dependent reactions of the photosynthetic energy convers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…The high electroactive area of PEDOT-NTs and all the advantages gained by the electrodeposition of AuNPs, such as durability, conductivity, and high superficial area, among others, make this modified electrode a perfect choice for the development of supercapacitors, as both capacitive and faradaic currents are enhanced in the presence of AuNPs. To verify the pseudocapacitance properties of the modified electrodes, the electrolyte was changed to 1 mol L –1 Na 2 SO 4 , which is more common for this type of device. , The electrochemical characterization is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The high electroactive area of PEDOT-NTs and all the advantages gained by the electrodeposition of AuNPs, such as durability, conductivity, and high superficial area, among others, make this modified electrode a perfect choice for the development of supercapacitors, as both capacitive and faradaic currents are enhanced in the presence of AuNPs. To verify the pseudocapacitance properties of the modified electrodes, the electrolyte was changed to 1 mol L –1 Na 2 SO 4 , which is more common for this type of device. , The electrochemical characterization is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…To verify the pseudocapacitance properties of the modified electrodes, the electrolyte was changed to 1 mol L −1 Na 2 SO 4 , which is more common for this type of device. 59,60 The electrochemical characterization is shown in Figure 6.…”
Section: Biosensor Developmentmentioning
confidence: 99%
“…Because of its photoreactivity, PEDOT:PSS is known to generate photocurrents in response to photon absorption . Recently, several research efforts using PEDOT:PSS in photosynthetic energy conversion has been reported including multilayered PEDOT:PSS-PSI films and PEDOT:PSS-modified PEC cells. , Since the PEDOT:PSS in such hybrid BPEC cells also absorbs photons in a broad wavelength range and produces electricity, , use of PEDOT:PSS as a PE conducting material can enhance the overall performance of BPEC systems . In fact, in this study, a fair portion of photocurrents obtained by our 3D printed TM/PEDOT:PSS BPEC system also originated from PEDOT:PSS energy conversion.…”
Section: Discussionmentioning
confidence: 99%
“…In general, organic materials and inorganic materials are two main categories of RS medium, as illustrated in Figure 6. Research of RS medium based on organic materials mainly focuses on biological materials (silk protein/fibroin, nanocellulose and albumen) [65][66][67], polymer materials (PVK (polyvinyl carbazole), PVA (polyvinyl alcohol), PDA (Polydiacetylene), PTH (polythiophene)) [68][69][70][71], and other materials. Chen et al presented an RRAM device fabricated with spin-coated chicken egg albumen layer [67].…”
Section: Thin Film Materials Of Rs Mediummentioning
confidence: 99%